Evidence-based efficacy, safety and technical features of performing percutaneous nephrolithotomy (systematic review of meta-analyses) - V. A. Malkhasyan; N. K. Gadzhiev; S. O. Sukhikh; D. Yu. Pushkar (Вестник урологии)
To date, the literature presents a wide data regarding the eﬀectiveness, safety, and technical features of percutaneous nephrolithotomy. A signiﬁcant proportion of studies are presented in the format of systematic literature reviews and meta-analyses. This article presents an analysis of the accumulated data was carried out in the form of a systematic review of meta-analyses.